Equity in health and justice: a look at the Brazilian Unified Health System (SUS) from the perspective of John Rawls - Machado Martins, Luiz Oscar; Fernandes dos Reis, Marcio; Chaoubah, Alfredo; Rego, Guilhermina (Acta Bioethica, 2023)
This study addresses the issue of equity in health and justice from the perspective of public health bioethics, describing the Brazilian Unified Health System (SUS), equating legitimate interests for essential goods, such as health. The conception of John Rawls’ theory of justice is “justice as fairness” and has a seventeenth century contractualism tenor. Although it was not conceived specifically for health and marked by the “difference principle”, it promoted, in the field of health care, the institution of health systems created on the basis of universal access and equity in the distribution of scarce resources. The principles of the Brazilian Unified Health System (SUS) guarantee access to all levels of care, equality in health care, without distinctions or privileges of any kind, integrity in health care, free of charge, community participation and decentralization, regionalization and hierarchization of health actions and services, which gives the SUS a strong Rawlsian bias. The Brazilian model was built on the principle that health is a right of all and a duty of the State, therefore, it is based on the assumption of universal and equal access to health actions and services for its promotion and recovery.